Form And Pragmatic Meaning Of Simuane Tallang Speech At The Rambu Solo' Ceremony For The Toraja People - Anastasia Baan (Universitas Cokroaminoto Palopo, 2023)
This study aims to describe the form and pragmatic meaning of Simune Tallang's speech in Rambu Solo' ceremony for Toraja people by using pragmatic approach. This type of research uses qualitative research. The source of data in this research is sourced from sources who are involved in the world of tomina who really understand the simuane tallang speech of the Toraja people. In collecting data, the techniques used are interview techniques, recording techniques, note-taking techniques and documentation techniques. The results of this study indicate that the form and pragmatic meaning of simuane tallang speech at the rambu solo' traditional ceremony for the Toraja people are speeches whose forms are intertwined and have the same meaning in the form of gratitude, advice, and hope.